High-Si-content cold-sprayed Al-Mg-Si composite coating and preparation method thereof
Through the preparation of a high Si content cold spray Al-Mg-Si composite coating, the problem of insufficient corrosion resistance and strength of Al-Mg-Si alloy in the marine field is solved, and the coating with high density and excellent corrosion resistance is achieved Layer, suitable for steel corrosion protection in complex environments.
Patent Information
- Application Number
- CN202411306979.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-19
AI Technical Summary
Al-Mg-Si alloy has problems such as tissue stability, poor formability, performance changes and elemental influence at high Si content, resulting in insufficient corrosion resistance and strength in its application in the marine field.
Using high Si content cold spray Al-Mg-Si composite coating and its preparation method, the substrate is pretreated and mechanically mixed and cold sprayed using spherical Al powder, Mg powder, Si powder and Al2O3 ceramic powder, followed by vacuum encapsulation and Diffusing annealing heat treatment to prepare a coating with high density and excellent corrosion resistance.
It realizes solid-state deposition at low temperature, reduces the porosity of the coating, enhances the protection effect, improves the mechanical properties of the coating and inhibits corrosion rate, and has a simple process and is suitable for long-term corrosion protection of steel in complex environments.
Smart Images

Figure CN119194437A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material anticorrosion, and particularly relates to a high-Si content cold-sprayed Al-Mg-Si composite coating and a preparation method thereof. Background Art
[0002] Corrosion is one of the main causes of steel material failure. Corrosion protection is particularly important for structural materials of marine equipment that are exposed to harsh environments such as the marine atmosphere for a long time. There are many means of steel protection, and the most widely used is metal protective coating. Cold spraying is a spraying technology that uses high-pressure gas to carry powder particles into the spray gun from the axial direction to generate a supersonic airflow. After the powder particles are accelerated by the airflow, they hit the surface of the substrate in a completely solid state, causing large plastic deformation and depositing on the surface of the substrate to form a coating. Compared with coating technologies such as hot dip plating, thermal spraying, and laser cladding, the operating temperature required for cold spraying is lower, and the phase change, oxidation, grain growth and other phenomena in the coating preparation process have been effectively improved.
[0003] Due to its abundant reserves and obvious passivation effect, Al has become one of the preferred materials for metal protective coatings. However, the passivation film of Al coating will be destroyed by Cl in seawater. - The damage eventually develops into pitting. In order to improve the anode performance of Al, elements such as Mg and Si are often added. Adding an appropriate amount of Mg element can not only improve the sacrificial ability of the coating, but also reduce the accumulation of corrosion products to form a harder shell-like protective layer, which greatly improves the corrosion resistance and service life of the coating. The addition of Si can form a dense protective film, effectively cut off the contact between water and oxygen and the metal, and inhibit the corrosion rate. Especially in the metal section, since the cut surface will expose the metal substrate, red rust may occur in the early stage, but over time, the effect of Si will cause the components of the coating to dissolve, forming a dense protective film, thereby inhibiting the corrosion of the section.
[0004] The Al-Mg-Si material disclosed in “The effect of Mg and Si content on the microstructure, texture and bendability of Al-Mg-Si alloys” has the following deficiencies:
[0005] (1) Structural stability problem: When the content of certain elements (such as strontium) in the alloy is too high, needle-like phases will be generated. These phases will aggregate at the grain boundaries, which will reduce the electrical conductivity and mechanical properties of the alloy.
[0006] (2) Poor formability: Aluminum alloys have relatively poor formability, especially when undergoing certain specific forming processes (such as 180° flanging), they are prone to cracking. This is mainly due to the influence of factors such as the alloy texture, the morphology, size and quantity of the Fe-containing phase, the size of the recrystallized grains, and the precipitation phase at the grain boundary.
[0007] (3) Performance changes during processing: During the processing, such as solution treatment and aging treatment, the performance of the alloy will be affected by many factors, such as temperature and time. Inappropriate processing conditions may lead to degradation of alloy performance, such as overburning and uneven distribution of precipitation phases.
[0008] (4) Influence of alloying elements: The content and type of elements in the alloy have a significant effect on the properties of the alloy. For example, an increase in Cu content will reduce its plasticity.
[0009] Therefore, on the basis of ensuring excellent forming and casting properties, the development of Al-Mg-Si materials with both high strength and excellent corrosion resistance is of great significance to the development of the shipbuilding field. Summary of the invention
[0010] In order to overcome the deficiencies in the prior art, the present invention provides a high Si content cold sprayed Al-Mg-Si composite coating and a preparation method thereof.
[0011] The preparation method of the cold sprayed Al-Mg-Si composite coating with high Si content comprises the following specific steps:
[0012] (1) Pretreatment of the substrate;
[0013] First, acetone ultrasonic cleaning is used to remove oil stains, and then corundum is used for sandblasting to remove rust and increase the surface roughness of the substrate, wherein the substrate includes Q235 steel.
[0014] (2) cold spraying the composite powder on the pretreated substrate;
[0015] The composite powder was obtained using spherical Al powder, Mg powder, Si powder and Al2O3 ceramic powder as raw materials (all raw materials were purchased from Beijing Tianchengyu Company);
[0016] The composition of the composite powder according to the mass percentage of the elements is: Al is 70-85wt.%, Mg is 7-10wt.%, Si is 5-20wt.%, and the addition amount of Al2O3 ceramic powder is 10%wt of the total mass of spherical Al powder, Mg powder and Si powder.
[0017] The composite powder is obtained by fully and evenly mixing aluminum powder, magnesium powder, silicon powder and Al2O3 ceramic powder by mechanical mixing and stirring for not less than 30 minutes, and then the powder is bagged, evacuated and placed in a vacuum drying oven at 70°C for 2 hours.
[0018] During the cold spraying process, the powder feeding gas and working gas are compressed air, the spraying angle is 90°, the gas pressure is 0.99 MPa, the gas heating temperature is 400°C, and the powder feeding amount is 50 g / min.
[0019] During cold spraying, the distance between the spray gun and the substrate surface is 12 mm, and the relative movement speed between the spray gun and the substrate is 5 to 8 mm / s.
[0020] (3) The Al-Mg-Si composite coating is vacuum packaged, and then diffusion annealed at 400-600° C. for 8 hours, taken out and air-cooled to room temperature to obtain a heat-treated coating.
[0021] The cold sprayed Al-Mg-Si composite coating obtained by the invention is applied to long-term corrosion protection of steel in various complex environments such as atmosphere and ocean.
[0022] Beneficial effects of the present invention:
[0023] (1) The present invention adopts cold spraying technology to prepare the coating at a low working temperature, has the characteristics of solid deposition at low temperature, has little thermal impact on the substrate, no oxidation, grain growth, phase change occurs during the spraying process, and has low residual tensile stress.
[0024] (2) The present invention adopts a cold spraying process to prepare the target coating, which is simple in process; the added Al2O3 ceramic phase powder can reduce the porosity of the coating and increase the density of the tissue.
[0025] (3) The present invention adds an appropriate amount of Si element, which further enhances the protective effect of the coating, improves the ability of the coating to inhibit the corrosion rate and improves the mechanical properties of the composite material.
[0026] (4) In the present invention, heat treatment of the coating at the selected annealing temperature can enhance the coating performance without affecting the performance of the body itself. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a cross-sectional scanning electron microscope image of the Al-Mg-8Si coating prepared in Example 1 of the present invention.
[0028] Figure 2 This is a cross-sectional scanning electron microscope image of the Al-Mg-12Si coating prepared in Example 2 of the present invention.
[0029] Figure 3This is a cross-sectional scanning electron microscope image of the Al-Mg-16Si coating prepared in Example 3 of the present invention.
[0030] Figure 4 This is a cross-sectional scanning electron microscope image of the Al-Mg-20Si coating prepared in Example 4 of the present invention.
[0031] Figure 5 This is a cross-sectional scanning electron microscope image of the Al-Mg-12Si coating prepared in Example 5 of the present invention.
[0032] Figure 6 This is a cross-sectional scanning electron microscope image of the Al-Mg-12Si coating prepared in Example 6 of the present invention.
[0033] Figure 7 This is a cross-sectional scanning electron microscope image of the Al-Mg-12Si coating prepared in Example 7 of the present invention.
[0034] Figure 8 This is a cross-sectional scanning electron microscope image of the Al-Mg-1Si coating prepared in Comparative Example 1 of the present invention.
[0035] Fig. 9 This is a cross-sectional scanning electron microscope image of the Al-Mg-12Si coating prepared in Comparative Example 2 of the present invention.
[0036] Fig.10 The electrochemical test results of the Al-Mg-Si composite coatings in the embodiments of the present invention and the comparative examples after being immersed in a 3.5% NaCl solution for 480 hours.
[0037] Fig.11 The hardness test results of the Al-Mg-Si composite coatings in various embodiments of the present invention and comparative examples are shown. DETAILED DESCRIPTION
[0038] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0039] Example 1
[0040] (1) Build an XY automation platform and check the operation of the spraying robot;
[0041] (2) Using acetone to ultrasonically clean the Q235 steel substrate to remove oil stains;
[0042] (3) Use corundum for sandblasting to remove rust and increase the surface roughness of the substrate;
[0043] (4) Prepare the ingredients in a weight ratio of 85wt.%, 7wt.% Mg, and 8wt.% Si, then add spherical Al powder, Mg powder, and Si powder with a total weight of 10%wt Al2O3 ceramic powder, mix well, and then put into a vacuum drying oven for 2 hours.
[0044] (5) The powder feeding gas is compressed air, the spraying angle is 90°, the gas pressure is 0.99 MPa, the powder feeding temperature is 400°C, the powder feeding amount is 50 g / min, the distance between the spray gun and the substrate is 12 mm, and the spray gun moving speed is 6 mm / s. These parameters are used to prepare the cold spray composite coating;
[0045] (6) After shaping treatment and strict inspection and acceptance, the cold-sprayed Al-Mg-Si composite coating is obtained.
[0046] (7) The sample was packaged in vacuum and subjected to diffusion annealing heat treatment at 500°C for 8 hours, and then taken out and air-cooled to room temperature.
[0047] (8) Use a solder gun to solder the wires and seal with resin to expose only the test surface.
[0048] (9) The encapsulated samples were immersed in a 3.5% NaCl solution for 480 h and electrochemical tests were performed.
[0049] (10) Two batches of samples were encapsulated using hot mounting powder, and only the exposed test surface was subjected to a neutral salt spray test using 5% NaCl solution;
[0050] Hardness test was performed using a microhardness tester.
[0051] Example 2
[0052] (1) Build an XY automation platform and check the operation of the spraying robot;
[0053] (2) Using acetone to ultrasonically clean the Q235 steel substrate to remove oil stains;
[0054] (3) Use corundum for sandblasting to remove rust and increase the surface roughness of the substrate;
[0055] (4) Prepare the ingredients in a weight ratio of 81wt.%, 7wt.% Mg, and 12wt.% Si, then add spherical Al powder, Mg powder, and Si powder with a total weight of 10%wt Al2O3 ceramic powder, mix well, and then put into a vacuum drying oven for 2 hours.
[0056] (5)-(10) Same as Example 1;
[0057] Hardness test was performed using a microhardness tester.
[0058] Example 3
[0059] (1) Build an XY automation platform and check the operation of the spraying robot;
[0060] (2) Using acetone to ultrasonically clean the Q235 steel substrate to remove oil stains;
[0061] (3) Use corundum for sandblasting to remove rust and increase the surface roughness of the substrate;
[0062] (4) Prepare the ingredients in a weight ratio of 77wt.%, 7wt.% Al, 7wt.% Mg, and 16wt.% Si, then add spherical Al powder, Mg powder, and Si powder with a total weight of 10%wt Al2O3 ceramic powder, mix well, and then put into a vacuum drying oven for 2 hours.
[0063] (5)-(10) Same as Example 1;
[0064] Hardness test was performed using a microhardness tester.
[0065] Example 4
[0066] (1) Build an XY automation platform and check the operation of the spraying robot;
[0067] (2) Using acetone to ultrasonically clean the Q235 steel substrate to remove oil stains;
[0068] (3) Use corundum for sandblasting to remove rust and increase the surface roughness of the substrate;
[0069] (4) Prepare the ingredients in a weight ratio of 73wt.%, 7wt.% Mg, and 20wt.% Si, then add spherical Al powder, Mg powder, and Si powder with a total weight of 10%wt Al2O3 ceramic powder, mix well, and then put into a vacuum drying oven for 2 hours.
[0070] (5)-(10) Same as Example 1;
[0071] Hardness test was performed using a microhardness tester.
[0072] Example 5
[0073] (1) Build an XY automation platform and check the operation of the spraying robot;
[0074] (2) Using acetone to ultrasonically clean the Q235 steel substrate to remove oil stains;
[0075] (3) Use corundum for sandblasting to remove rust and increase the surface roughness of the substrate;
[0076] (4) Prepare the ingredients in a weight ratio of 79wt.%, 9wt.%, Mg9wt.%, and 12wt.% of Si, then add spherical Al powder, Mg powder, and Si powder with a total weight of 10%wt of Al2O3 ceramic powder, mix well, and then put into a vacuum drying oven for 2 hours.
[0077] (5)-(10) Same as Example 1;
[0078] Hardness test was performed using a microhardness tester.
[0079] Example 6
[0080] (1) Build an XY automation platform and check the operation of the spraying robot;
[0081] (2) Using acetone to ultrasonically clean the Q235 steel substrate to remove oil stains;
[0082] (3) Use corundum for sandblasting to remove rust and increase the surface roughness of the substrate;
[0083] (4) Prepare the ingredients in a weight ratio of 81wt.%, 7wt.% Mg, and 12wt.% Si, then add spherical Al powder, Mg powder, and Si powder with a total weight of 10%wt Al2O3 ceramic powder, mix well, and then put into a vacuum drying oven for 2 hours.
[0084] (5) The powder feeding gas is compressed air, the spraying angle is 90°, the gas pressure is 0.99 MPa, the powder feeding temperature is 400°C, the powder feeding amount is 50 g / min, the distance between the spray gun and the substrate is 12 mm, and the spray gun moving speed is 6 mm / s. These parameters are used to prepare the cold spray composite coating;
[0085] (6) After shaping treatment and strict inspection and acceptance, the cold-sprayed Al-Mg-Si composite coating is obtained.
[0086] (7) The sample was packaged in vacuum and subjected to diffusion annealing heat treatment at 400°C for 8 hours, and then taken out and air-cooled to room temperature.
[0087] (8)-(10) Same as Example 1;
[0088] Hardness test was performed using a microhardness tester.
[0089] Example 7
[0090] (1) Build an XY automation platform and check the operation of the spraying robot;
[0091] (2) Using acetone to ultrasonically clean the Q235 steel substrate to remove oil stains;
[0092] (3) Use corundum for sandblasting to remove rust and increase the surface roughness of the substrate;
[0093] (4) Prepare the ingredients in a weight ratio of 81wt.%, 7wt.% Mg, and 12wt.% Si, then add spherical Al powder, Mg powder, and Si powder with a total weight of 10%wt Al2O3 ceramic powder, mix well, and then put into a vacuum drying oven for 2 hours.
[0094] (5) The powder feeding gas is compressed air, the spraying angle is 90°, the gas pressure is 0.99 MPa, the powder feeding temperature is 400°C, the powder feeding amount is 50 g / min, the distance between the spray gun and the substrate is 12 mm, and the spray gun moving speed is 6 mm / s. These parameters are used to prepare the cold spray composite coating;
[0095] (6) After shaping treatment and strict inspection and acceptance, the cold-sprayed Al-Mg-Si composite coating is obtained.
[0096] (7) The sample was packaged in vacuum and subjected to diffusion annealing heat treatment at 600°C for 8 hours, and then taken out and air-cooled to room temperature.
[0097] (8)-(10) Same as Example 1;
[0098] Hardness test was performed using a microhardness tester.
[0099] Comparative Example 1
[0100] (1) Build an XY automation platform and check the operation of the spraying robot;
[0101] (2) Using acetone to ultrasonically clean the Q235 steel substrate to remove oil stains;
[0102] (3) Use corundum for sandblasting to remove rust and increase the surface roughness of the substrate;
[0103] (4) Prepare the ingredients in a weight ratio of Al 92wt.%, Mg 7wt.%, and Si 1wt.%, then add spherical Al powder, Mg powder, and Si powder with a total weight of 10%wt of Al2O3 ceramic powder, mix well, and then put into a vacuum drying oven for 2 hours.
[0104] (5) The powder feeding gas is compressed air, the spraying angle is 90°, the gas pressure is 0.99 MPa, the powder feeding temperature is 400°C, the powder feeding amount is 50 g / min, the distance between the spray gun and the substrate is 12 mm, and the spray gun moving speed is 6 mm / s. These parameters are used to prepare the cold spray composite coating;
[0105] (6) After shaping treatment and strict inspection and acceptance, the cold-sprayed Al-Mg-Si composite coating is obtained.
[0106] (7) The sample was packaged in vacuum and subjected to diffusion annealing heat treatment at 500°C for 8 hours, and then taken out and air-cooled to room temperature.
[0107] (8) Use a solder gun to solder the wires and seal with resin to expose only the test surface.
[0108] (9) The encapsulated samples were immersed in a 3.5% NaCl solution for 480 h and electrochemical tests were performed.
[0109] (10) Two batches of samples were encapsulated using hot mounting powder, and only the exposed test surface was subjected to a neutral salt spray test using 5% NaCl solution.
[0110] Hardness test was performed using a microhardness tester.
[0111] The scanning electron microscope image of the cross section of the heat-treated cold-sprayed Al-Mg-Si composite coating obtained in step (7) of Comparative Example 1 is as follows: Figure 8 As shown, the scanning electron microscopy results show that after long-term heat treatment, the coating with low Si content becomes loose and has obvious cracks.
[0112] Comparative Example 2
[0113] (1) Build an XY automation platform and check the operation of the spraying robot;
[0114] (2) Using acetone to ultrasonically clean the Q235 steel substrate to remove oil stains;
[0115] (3) Use corundum for sandblasting to remove rust and increase the surface roughness of the substrate;
[0116] (4) Prepare the ingredients in a weight ratio of 81 wt.% Al and 7 wt.% Mg and 12 wt.% Si, mix them thoroughly and dry them in a vacuum drying oven for 2 hours.
[0117] (5) The powder feeding gas is compressed air, the spraying angle is 90°, the gas pressure is 0.99 MPa, the powder feeding temperature is 400°C, the powder feeding amount is 50 g / min, the distance between the spray gun and the substrate is 12 mm, and the spray gun moving speed is 6 mm / s. These parameters are used to prepare the cold spray composite coating;
[0118] (6) After shaping treatment and strict inspection and acceptance, the cold-sprayed Al-Mg-Si composite coating is obtained.
[0119] (7) The sample was packaged in vacuum and subjected to diffusion annealing heat treatment at 500°C for 8 hours, and then taken out and air-cooled to room temperature.
[0120] The scanning electron microscope image of the cross section of the heat-treated cold-sprayed Al-Mg-Si composite coating obtained in step (7) of Comparative Example 2 is as follows: Fig. 9 As shown, by comparing the scanning electron microscopy results with those of Example 2, it can be seen that the pores of the coating without adding Al2O3 ceramic powder are very obvious and numerous, indicating that the porosity is relatively high.
[0121] Performance Test:
[0122] Relevant performance tests were performed on the embodiments of the present invention and the comparative examples, and the test results are shown below.
[0123] (1) Vickers hardness test: the test standard is GB / T 4340.1-2024. Take one hot-mounted sample in step (10) of the embodiment and the comparative example respectively, and use 400 mesh, 1000 mesh and 2000 mesh sandpaper to grind the coating surface of the sample to be tested, so that the sample surface is smooth and scratch-free;
[0124] Then use the microhardness tester to test the hardness, select five points to calculate the average value, the results are shown in Table 1 and Fig.11 shown.
[0125] Table 1
[0126]
[0127] Conclusion: The hardness of the cold-sprayed Al-Mg-Si composite coatings increases first and then decreases with the increase of Si content. Increasing the Mg content and reducing the heat treatment temperature have little difference in hardness compared with Example 2. Increasing the heat treatment temperature in Example 7 makes the hardness of the coating much worse, but it can be seen that the hardness of the coatings prepared in the examples is higher than that of the coatings in Comparative Example 1.
[0128] The coating prepared in Example 2 has the highest hardness when the Si content is 12 wt.%.
[0129] (2) Neutral salt spray test: The test standard is GB / T 10125-2021. The hot-mounted samples in step (10) of the embodiment and the comparative example are cleaned with anhydrous ethanol and blown dry. The sample weight is weighed using an electronic balance. A 5 wt.% NaCl solution is prepared and added to a salt spray chamber. The sample is placed in the salt spray chamber for testing.
[0130] The temperature of the salt spray box was maintained at 35±1°C, pH=6.5-7.2, and the corrosion time was 480 hours. The results are shown in Table 2.
[0131] Table 2
[0132]
[0133] In this study, the weight gain method was used to measure the corrosion rate of the sample, and the calculation formula is:
[0134] V=(W2-W1)·S -1 ·T -1
[0135] Where, V: corrosion rate of galvanized sheet, unit: g·m-2 ·h -1
[0136] W1: weight of the sample before corrosion, g
[0137] W2: weight of the sample after corrosion, g
[0138] S: Sample exposure area, m 2
[0139] T: corrosion cycle, h
[0140] Conclusion: The corrosion rate of the cold sprayed Al-Mg-Si composite coating shows a trend of first decreasing and then increasing with the increase of Si content. The corrosion rate of the coating with increasing Mg content and reducing heat treatment temperature is not much different from that of Example 2. However, the corrosion rate of the coating is faster when the heat treatment temperature is increased in Example 7. In addition, when the Si content in Comparative Example 1 is only 1wt.%, the corrosion rate of the coating is 2.2869g / (m 2 .h), corrosion is too fast;
[0141] The salt spray corrosion rate of the Al-Mg-Si composite coating prepared in Example 2 is 1.181 g / (m 2 .h), at which point the corrosion rate is the lowest.
[0142] (3) Electrochemical test: The test standard is GBT40299-2021. The samples soaked in step (9) of the embodiment and the comparative example were subjected to electrochemical impedance test and potentiodynamic polarization curve test. The results are shown in Table 3 and Fig. 9 shown.
[0143] Table 3
[0144]
[0145] Conclusion: Among the examples and comparative examples, the coating prepared in Example 2 has the highest self-corrosion potential and the lowest self-corrosion current density, so it has the smallest corrosion tendency, the slowest corrosion rate and the best corrosion resistance.
[0146] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A high Si content cold sprayed Al-Mg-Si composite coating, characterized in that: The high Si content cold sprayed Al-Mg-Si composite coating is a coating obtained by cold spraying spherical Al powder, Mg powder, Si powder and Al2O3 ceramic mixed powder on a pretreated substrate and then subjecting it to heat treatment.
2. The high Si content cold sprayed Al-Mg-Si composite coating according to claim 1, characterized in that: The composition of the high Si content cold sprayed Al-Mg-Si composite coating is 70-85wt.%, Mg 7wt-10.%, Si 8-20wt.%, and the addition amount of Al2O3 ceramic powder is 10%wt of the total mass of spherical Al powder, Mg powder and Si powder.
3. A method for preparing a high Si content cold sprayed Al-Mg-Si composite coating as claimed in claim 1, characterized in that: The preparation method steps are as follows: (1) Pretreatment of the substrate; (2) cold spraying the composite powder on the pretreated substrate; (3) The Al-Mg-Si composite coating is vacuum packaged, and then diffusion annealing heat treatment is performed, and the heat-treated coating is obtained after cooling.
4. The method for preparing a high Si content cold sprayed Al-Mg-Si composite coating according to claim 3, characterized in that: The pretreatment of the substrate in step (1) is: first using acetone ultrasonic cleaning to remove oil stains, and then using white corundum to perform sandblasting to remove rust and increase the surface roughness of the substrate, wherein the substrate includes steel Q235.
5. The method for preparing a high Si content cold sprayed Al-Mg-Si composite coating according to claim 3, characterized in that: The composite powder in step (2) is obtained by fully mixing aluminum powder, magnesium powder, silicon powder and Al2O3 ceramic powder by mechanical mixing and stirring, and then the powder is bagged, evacuated and placed in a vacuum drying oven at 70°C for 2 hours.
6. The method for preparing a high Si content cold sprayed Al-Mg-Si composite coating according to claim 3, characterized in that: In the cold spraying process of step (2), the powder feeding gas and the working gas are compressed air, the spraying angle is 90°, the gas pressure is 0.99 MPa, the gas heating temperature is 400°C, and the powder feeding amount is 50 g / min.
7. The method for preparing a high Si content cold sprayed Al-Mg-Si composite coating according to claim 3, characterized in that: During the cold spraying process of step (2), the distance between the spray gun and the substrate surface is 12 mm, and the relative movement speed between the spray gun and the substrate is 5 to 8 mm / s.
8. The method for preparing a high Si content cold sprayed Al-Mg-Si composite coating according to claim 3, characterized in that: The diffusion annealing heat treatment in step (3) is: performing diffusion annealing heat treatment at 400-600° C. for 8 hours.
9. An application of the high Si content cold sprayed Al-Mg-Si composite coating as claimed in claim 1, characterized in that: The composite coating is used for long-term corrosion protection of steel in complex atmospheric and marine environments.
Citation Information
Patent Citations
Aluminum-based composite coating on magnesium alloy surface and preparation method of aluminum-based composite coating
CN111893478A
Alloy with Al-Si-Mg coating and preparation method thereof
CN114214614A
Process for manufacturing an aluminum alloy part
US20220112581A1
Cited By
Aluminum-based composite powder, preparation method thereof and cartridge receiver repairing method
CN121339424A
Powder composition for gas-dynamic spraying onto articles made of magnesium alloys
RU2862591C1